EVALUATION OF CALCULATION WORK VOLUME OF FGD AND ESP PLTU SURALAYA DEVELOPMENT PROJECTS USING THE AUTODESK REVIT APPLICATION - Napitupulu, Crystian Simon Yohanes (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2024)
In construction work, problems such as volume estimation, construction methods, and work interfaces often occur. Problems like this can be minimized with the Building Information Modeling (BIM) method. BIM changes conventional methods from being inefficient to integrated and collaborative processes. The various benefits and advantages of using BIM include the integration between design and construction. The application of BIM can minimize errors between design and construction. In BIM, we can define some modeling information, like coordinate, model view, clash detection, rebar schedule & detail fabrication, concrete volume, and others that are useful in the construction process. This study applies Autodesk Revit software for volume estimation and analyzes the differences in the BIM-based volume estimation results with conventional methods. The Revit software volume output is then compared to the existing or contracted Bill of Quantity (BOQ). The results of the evaluation show that the volume contains from the BIM calculation on the volume of concrete is 3056.31 m3 and the weight of the reinforcement bar is 540.18 tons, these results are different from the BOQ of the contract, each of which is 2765.11 m3 for concrete volume and 490.05 tons for reinforcement bar weight, which each has a shortage of 291.20 m3 and 52.64 tons.